(3GdYdGbI Hjf GdJYQV ddHQGeL GdQjGVjI h GJLGgGJ GdeQCI GdeUQjI fMh GdQjGVI GdfSGFjI (B/ s - (3gOi Wg jhSa jhSa GdTGPdis; (3gHI Gddg HgLJ GdSeQi (B: s ((3GdbGgQI (B: s (3gOi Wg jhSa jhSa GdTGPdi (B: s, 2019)
(3GSJgOaJ GdOQGSI JMOjO GdYdGbI Hjf GdJYQV ddHQGeL GdQjGVjI hGJLGgGJ GdeQCI GdeUQjI fMh GdQjGVI GdfSGFjI(B: (3ef NdGd GdJYQa Ydi MLe GdGgJeGe GdPi Jhdjg GdHQGeL GdQjGVjI(B: (3h QUO CfeGW GSJNOGe GdeQCI GdeUQjI ddHQGeL GdQjGVjI(B: (3h GMJjGLGJgG ef Jdc GdHQGeL(B: (3h GdETHGYGJ GdeJMbbI ef Pdc GdGSJNOGe(B. (3h bO Je JWHjb fXQjI GdGSJNOGeGJ h GdETHGYGJ(B: (3h fXQjI GdbjeI GdeJhbYI(B. (3h bO GSJNOeJ GdHGMKI GSJeGQI JMdjd eVehf ddHQGeL GdQjGVjI h GdJi TedJ (B(12) (3HQfGeLkG ef GdbfhGJ GdQjGVjI GdeUQjI(B: (3h cPdc GSJNOGe GSJeGQI GSJHjGf(B: (3h bO oCLQi GdGSJHjGf Ydi YjfI YeOjI bhGegG (B(400) (3ef GdaJjGJ h GdfSGA GddhGJi JTGgOf GdHQGeL GdQjGVjI OGNd LeghQjI eUQ GdYQHjI(B. (3h bO GfJgJ GdOQGSI Edi Cf GdHQGeL GdQjGVjI JgeT GdQjGVI GdfSGFjI(B: (3MjK bGeJ HJZWjI CNHGQ GdQjGVI GdfSGFjI HhGbY SGYJjf h(B43 (3ObjbI abW(B: (3ai ebGHd (B83 (3SGYI h(B42 (3ObjbI dCNHGQ h bVGjG GdQjGVI GdQLGdjI(B: (3h gPG bO COi Edi GfNaGV eYOd GdJYQV ddHQGeL GdQjGVjI Hjf GdeHMhKGJ YjfI GdOQGSI(B: (3ceG CXgQJ GdfJGFL Cf gfGc fSHI YGdjI ef GdeHMhKGJ dG jeGQSf GdQjGVI(B: (3h bO QCJ GdCZdHjI efgf Cf GdHQGeL GdQjGVjI dG JTLYgf Ydi eeGQSI GdQjGVI(B: (3h HGdQZe ef Pdc GJVM hLhO GJLGgGJ EjLGHjI fMh GdQjGVI GdfSGFjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdEPGYI h GdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSJNOGeGJ h GdETHGYGJs; (3GdHQGeL GdQjGVjIs; (3GdJYQVs